براہوئی انشائیہ ٹی راجی ویل نا درک: Identification of Social Issues in Brahui Inshaaiya - Aysha Wahab (Al-Burz, 2019)
Brahui fiction has its dimensions, beside Novel, Short Story and Drama, the fourth part of Brahui fiction is known as “Inshaeya”. The word inshaeya can be translated as Essay. It can be describing as the shortest form of Short Story. the Brahui essay is a part of fiction. The purpose of writing this title is to identify social issues of the community in inshaeya. the history of shortest short story in Brahui commenced from 1960. When “Shirookh” published by Mr. Kamil-ul- Qadri, the decade of 60ties opened corridor for Brahui Inshaeya, after Qadri the local writers had worked on inshaeya. it is a part of Brahui fiction now. This paper has it objected to identified the inshaeya that the social problems have been addressed in. a qualitative research methodology has been adopted to complete this paper, the mod of this paper by topic is descriptive research. And the secondary source of data has been used and it has limited with the work of Mr. Kamil-ul-Qadri, Haji Abdul Latif Bangulzai, Prof. Khudaedad Gul, Mr. Arif Zia and Mr. Ghamkhwar Hayat in premises of Sarawan. This ends with the question why the work on ishaeya is slow in Brahui then the Short Story.